Regioselective N‐Alkylation of Ethyl 4‐Benzyloxy‐1, 2, 3‐triazolecarboxylate: A Useful Tool for the Synthesis of Carboxylic Acid Bioisosteres. (14th December 2018) - Sainas, Stefano; Pippione, Agnese C.; Giraudo, Alessandro; Martina, Katia; Bosca, Federica; Rolando, Barbara; Barge, Alessandro; Ducime, Alex; Federico, Antonella; Grossert, Stuart J.; White, Robert L.; Boschi, Donatella; et al.
Abstract : Acidic 4‐hydroxy‐1, 2, 3‐triazole is a proven bioisostere of acidic functions that has recently been used to replace the acidic moieties of biologically active leads. Straightforward chemical strategies for the synthesis of the three possible N‐alkylated 4‐hydroxy‐1, 2, 3‐triazole regioisomers have been designed and reported herein, by identifying the optimal conditions under which the alkylation of ethyl 4‐benzyloxy‐1, 2, 3‐triazolecarboxylate (compound19 ) can be regiodirected to the triazole N(b) position and thus produce the only isomer that cannot be obtained via the cycloaddition reaction. Furthermore, an innovative platform for parallel synthesis, called Arachno and which has been patented by the authors' group, has been used to speed up the process, and an NMR study has been carried out to better understand the reactivity of compound19 towards the N(b) position. A library of benzyloxy protected 4‐hydroxy‐1, 2, 3‐triazoles has been prepared using the two strategies: regiodirection for the N(b) and N(c) isomers and cycloaddition for the N(a) isomers; the processes are described herein. The three N‐alkylated regioisomer series have been characterized spectroscopically (NMR and MS). The subsequent catalytic hydrogenation of the 4‐benzyloxy protective group on the N‐alkylated‐4‐benzyloxy‐5‐ethoxycarbonyl‐1, 2, 3‐triazoles provided the corresponding substituted 4‐hydroxy‐1, 2, 3‐triazoles. Abstract :